2020
DOI: 10.1111/ped.14237
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous sulfate oral solution in young children with iron deficiency anemia: An open‐label trial of efficacy, safety, and acceptability

Abstract: Background This study evaluated the efficacy, safety, and acceptability of a new ferrous sulfate oral solution (Tardyferon® 20 mg/mL) in young children with mild or moderate iron deficiency anemia (IDA). Methods This was a multicenter, national, single‐arm, open‐label study. Children aged 6–53 months presenting with mild or moderate IDA (i.e., blood hemoglobin (Hb) ranging from 7.0 to 10.9 g/dL and serum ferritin <12 ng/mL) were eligible for inclusion. The ferrous sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Of particular interest is ferrous ascorbate, which is the drug of choice for the treatment of iron deficiency anaemia, especially in developing countries like India. For example, doses of 3–6 mg/kg/day of ferrous ascorbate for 12 weeks in children have led to substantial increases in haemoglobin levels of about 4–5 g/dL, which was thus more efficient than other iron formulations including iron polymaltose and ferrous sulfate [ 189 , 190 , 191 , 192 ].…”
Section: The Role Of Ascorbic Acid In Iron Absorption and Iron Excmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is ferrous ascorbate, which is the drug of choice for the treatment of iron deficiency anaemia, especially in developing countries like India. For example, doses of 3–6 mg/kg/day of ferrous ascorbate for 12 weeks in children have led to substantial increases in haemoglobin levels of about 4–5 g/dL, which was thus more efficient than other iron formulations including iron polymaltose and ferrous sulfate [ 189 , 190 , 191 , 192 ].…”
Section: The Role Of Ascorbic Acid In Iron Absorption and Iron Excmentioning
confidence: 99%
“…The ascorbic acid interactions with different oral, intramuscular and intravenous iron formulations are of pharmacological, toxicological and clinical importance [ 205 , 206 ]. There are many ferrous and ferric iron formulations available, such as oral ferrous sulfate, ferrous gluconate, ferric fumarate, ferric polymaltose, ferric maltol, ferric iron dextran, ferric iron sucrose, ferric gluconate, ferric saccharate, etc., used for treating many categories of iron-deficient patients [ 190 , 191 , 192 , 207 ]. While oral iron formulations may be beneficial for patients given the increase of iron absorption in the presence of ascorbic acid, there is no advantage to using vitamin C during intramuscular and intravenous administration of different iron formulations, given the increasing prospects of pro-oxidant and other toxicity [ 208 , 209 ].…”
Section: Drug Interactions With Ascorbic Acid and Ironmentioning
confidence: 99%
“…Hb value may normalize on a small daily dose of iron, but this low dose seldom suffices for metabolic needs or the replenishment of iron stores in the body [ 13 ]. Similar studies of iron supplementation in children have reported higher efficacies within a 3-month supplementation period; however, much higher doses of iron (ranging from 2 mg/kg of iron per body weight per day to 6 mg/kg of iron per body weight per day) than the one applied in our study have been used [ 14 , 15 , 16 ]. Of particular importance, these studies were all performed in anemic subjects, whereas our study included children with ID without anemia.…”
Section: Discussionmentioning
confidence: 88%
“…It has taken almost forty years to reach the clinical stage from the original discovery and from initial biochemical and other preclinical studies, which proposed the mechanisms of efficient iron delivery from iron complexes to cells, animals and humans [128][129][130][131]. Improvements have also been reported in the treatment of iron deficiency anemia using many other ferric and ferrous iron formulations and also different administration protocols [300][301][302][303].…”
Section: Future Prospectsmentioning
confidence: 99%